Cyclic Depsipeptides and Linear Peptides With Cytotoxic and Antiphytopathogenic Activities From Symbiotic Bacteria of Xenorhabdus (Enterobacteriales: Morganellaceae) Genus. (17th December 2022) - Zolfaghariyan, Sahar; Shakeri, Abolfazl; Asili, Javad; Tarighi, Saeed; Grün, Peter; Shi, Yi-Ming; Bode, Helge B; Karimi, Javad
Abstract: On the basis of biological activities of the ethyl acetate extracts of four Xenorhabdus sp., including Xenorhabdus nematophila FUM 220, Xenorhabdus nematophila FUM 221, Xenorhabdus bovienii FUM 222, and Xenorhabdus bovienii FUM 223, X. nematophila FUM 220 was preferentially selected to track the isolation of responsible compounds. Chemical study on the ethyl acetate extract of X. nematophila isolate FUM220 which is derived from the native nematode Steinernema carpocapsae (Rhabditida: Steinernematidae), was evaluated, and eleven compounds, including xenocoumacin II (1 ), xenortide-396 (2 ), xenortide A (3 ), xenortide-410 (4 ), xenortide-449 (5 ), xenematide A 663 (6 ), rhabdopeptide-574 (7 ), rhabdopeptide-588 (8 ), rhabdopeptide-687 (9 ), rhabdopeptide-701 (10 ), and nematophin-273 (11 ) were characterized. In this experimental study, we surveyed the antitumoral potential of bacterial extract and bacterial metabolites to treat human breast cancer (MCF-7), human lung cancer (A549), and murine Tumor (B16) cell lines. We observed that all samples were cytotoxic, but bacterial extracts of X. nematophila FUM 220 and X. bovienii FUM 223 showed higher toxicity on mentioned cell lines. Potent cytotoxic activity was found for compounds 6 and 11 with IC50 of 6.2 μg/ml against human lung cancer A549 cell lines, too. These compounds showed moderated antibacterial activity against Xanthomonas oryzae pv. oryzae strain Xoo-IR42 (Xanthomonadales: Xanthomonadaceae) (MIC of 62.5 μg/ml) and Staphylococcus aureus strain 1112 (Bacillales: Staphylococcaceae) (MIC of 100 μg/ml). The bacterial extracts from X. bovienii FUM 222 showed strong inhibition of the growth of S. aureus strain 1112, by a minimal inhibitory concentration assay (MIC of 53.5 μg/ml). Xenorhabdus genera produce metabolites with potent cytotoxic and antibacterial activity. Single compounds can be isolated, identified, and commercialized, but various species or strains may change their anticancer or antimicrobial potential. The present study brings new clues regarding the qualified of Xenorhabdus as future peptide sources for supplying natural bioactive compounds and challenge multidrug-resistant bacteria, treat cancer, and plant diseases. Graphical Abstract: